Experimental study of the protuberance effect on the blade performance of a small horizontal axis wind turbine - Huang, G.Y.; Shiah, Y.C.; Bai, C.J.; Chong, W.T. (2015)
The research aims to study the effect of leading edge protuberances on the blade performance at the stall region of the small-scale horizontal axis wind turbine (HAWT) with variable rotational speed. Experiments were carried out for the blades with smooth leading edge (baseline) as well as some comparative models with leading edge protuberances characterized by different sinusoidal amplitudes and wavelengths. The experiments were performed for the 3D static models to obtain the lift/drag coefficients. Additionally, rotor-blade models of the HAWT system were also tested separately to consider the rotation effect. From the experiments, the results indicated that the protuberant blades with smaller amplitudes possess better performance at the stall region as compared with the baseline model. (C) 2015 Elsevier Ltd. All rights reserved.